Pengaruh Model Pembelajaran Inquiry terhadap Pemahaman Konsep IPA Siswa SMA Negeri 1 Lotu Tahun Pelajaran 2023/2024 - Ferlina Lahagu; Agnes Renostini Harefa (GEN BIONIX: Jurnal Ilmiah Pendidikan Biologi, 2024)
Students’ low conceptual understanding in science learning remains a persistent challenge, often caused by teacher-centered approaches that limit active engagement and meaningful learning experiences. This study aims to examine the effect of the Inquiry learning model on students’ conceptual understanding in science at SMA Negeri 1 Lotu. The research employed a quasi-experimental design using a randomized pretest-posttest control group approach. A total of 52 eleventh-grade students participated in the study, divided into an experimental class taught using the Inquiry model and a control class taught using conventional methods. Data were collected through essay-based tests administered before and after the intervention and analyzed using descriptive and inferential statistics, including an independent t-test. The findings reveal that students in the experimental group demonstrated a higher improvement in conceptual understanding compared to those in the control group. The mean posttest score of the experimental class was significantly higher, indicating the effectiveness of the Inquiry model in facilitating deeper conceptual learning. The statistical analysis further confirmed a significant difference between the two groups, supporting the hypothesis that Inquiry-based learning positively influences students’ understanding of science concepts. These results highlight the importance of student-centered learning approaches in enhancing both cognitive outcomes and scientific thinking skills.